Membangun Karakter Kristiani Melalui Pembelajaran Aktif: Meneladani Yesus sebagai Guru Agung - Sitip, Martinus sulang; Loris Loris; Joni Joni; Lisna Novalia (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Identifying key principles in Jesus' teaching method that are relevant to the concept of active learning. Analyzing how these principles can be integrated into the practice of Christian character education for students. Exploring the potential impact of implementing an active learning model based on Jesus' example on the formation of Christian character in students. This study adopted a qualitative approach with a literature study design and narrative analysis. This method was chosen because of its ability to explore in depth abstract concepts and analyze narrative texts that are at the heart of Jesus' teaching. google scholer, especially the narrative of Jesus' teaching in the Gospels. Secondary data sources include academic literature on character education, active learning, and studies on Jesus' teaching method. Active learning is a way or strategy of learning that allows students to interact, solve problems, to learn naturally. The Active Learning Approach is a teaching strategy that encourages students to interact, solve problems, and achieve realization naturally. Active learning, often known as active learning, is a type of education in which students engage students who are active in the learning process. Actively participate in the learning process. This study shows that Jesus' teaching method offers an active learning model that is very relevant and effective for building Christian character. Key principles such as the use of imagery, reflective inquiry, direct experience, and contextualization can be effectively integrated into contemporary Christian character education practices.